Later exposure to different perch material and design affects behaviour and performance of Leghorn hens - ANWAR, Jabran; MAHMUD, Athar; ISHAQ, Hafiz Muhammad; Ahmad, S; KHAN, Ehsaan Ullah; WAQAS, Muhammad; USMAN, Muhammad; ZAID, Muhammad (Journal of the Hellenic Veterinary Medical Society, 2024)
Perching behaviour is natural and evident in Red Jungle fowl, from which modern-day chickens originated. A positive impact of perching in the improvement of a bird’s physical condition. In this experimental study, 540 LSL lite laying hens were randomly distributed according to Complete Randomized Design in 6 treatments with 6 replicates of 15 birds each. The experiment was set up as a 2 × 3 factorial arrangement of treatments; treatments consisted of 2 perch materials (wooden and plastic) and 3 perch shapes (square, round, and triangle). Effects of perch material and shape were evaluated on productive performance, behaviour and welfare traits, and egg characteristics. Egg weight was higher in wooden perch materials than plastic. Regarding perch design, egg weight, production percentage, and feed conversion ratio per kg of egg mass of commercial layers differed significantly. Moreover, wing flapping and perching behaviour were significant among different perch designs. Egg volume, egg weight, albumen height, Haugh unit score, and shell thickness differed significantly among perch designs. In conclusion, the provision of different perch designs especially wooden and triangular perches positively influences productivity, behaviour, and egg quality traits in laying birds.